Impacto do Tratamento Endodôntico na Qualidade de Vida - Avancini, Bruna Scarlot (2022)
Dental pain, caused by pulp and periapical diseases, can cause withdrawal from social, school or work activities, causing physical and psychological suffering, in addition to financial losses, thus having a negative impact on well-being and quality of life. individuals' lives. In view of this, endodontic treatment is shown to be an effective therapeutic option, of a conservative nature and capable of restoring function to the dental element. The aim of the present study was to analyze whether endodontic treatment is capable of promoting an improvement in quality of life. This is a prospective longitudinal study of uncontrolled intervention of the “before and after” type, which analyzed the impact on quality of life and associated socioeconomic factors, through the application of the OHIP-14 questionnaire before and after treatment. An initial sample composed of 312 participants who sought care at the endodontic clinic of ABO-ES was analyzed, and a final sample composed of 148 participants who completed endodontic treatment. The association between variables was verified by Fisher's exact test, to assess the strength of the association between the variables, the odds ratio (OR) was calculated, to analyze the effect of the combined dimensions of the OHIP-14 instrument, the test of Mantel-Haenszel. The comparison of the impact in the second moment in relation to the first was performed using the non-parametric Wilcoxon test. In the initial sample, 87.8% of the individuals declared impact, with the most reported domains being: psychological discomfort (76%) and physical pain (67.3%). The sociodemographic profile of the participants in the first sample was mostly female (63.1%), aged up to 43 years (51.6%), brown (45.5%), married or living with a partner (53.2%), residing in the municipality of Serra (51.3%), who studied for 13 years or more (78.9%), belonging to classes C/D/E (66%) and who used the Single System (SUS) to have access to oral health services in the last 12 months or who did not have access (53.2%). Impact predilection was associated with female individuals, non-white, living without a partner, who studied for 13 years or more, belonging to classes C/D/E and who access oral health services through the Unified System (SUS) or who do not have access. In the final sample, the demographic profile of the analyzed population was mostly female (59.5%), aged up to 43 years (53%), mixed race (45.3%), married or living with a partner. (54.1%), residing in the municipality of Serra (51.3%), who declared having studied for 13 years or more (83%), belonging to classes C/D/E (62.9%) and having used private services to access oral health services in the last 12 months prior to the survey (54.1%). The impact on quality of life after endodontic treatment was reported by only 10 people (6.8%), and the domains with the greatest impact reported after treatment were psychological discomfort (3.4%), physical pain (3 .4%) and psychological disability (3.4%). It was possible to observe a decrease in the impact frequency in all domains analyzed by the OHIP-14, and also a decrease in the general frequency of 92.3% in a period of one month. The findings of this study prove the ability of endodontic treatment to improve quality of life and can guide the creation of public health policies aimed at increasing universal access to this therapy.